2019
DOI: 10.1136/bmjopen-2018-026413
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to cervical cancer screening among rural women in eastern China: a qualitative study

Abstract: ObjectivesTo explore barriers to free cervical cancer screening among rural women in China from the perspective of women, healthcare providers and women’s husbands to inform intervention planning.DesignA qualitative study framed around potential policy and practice options, drawing on the concepts of descriptive phenomenology and implementation research.SettingThis study was carried out at township level within two counties in Jining Prefecture of eastern China.Participants and data collectionSemi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 40 publications
6
53
1
Order By: Relevance
“…Working women are more likely to perform PS because of having higher level of outcome, and accessing richer information and scientific resources. However, housewives are less likely to perform the above test due to their lower participation in the society and, as a result, their lack of awareness and financial dependence on their spouses [ 45 ]. Structural barriers such as low household incomes are an important determinant and make men unable to provide financial support to women.…”
Section: Resultsmentioning
confidence: 99%
“…Working women are more likely to perform PS because of having higher level of outcome, and accessing richer information and scientific resources. However, housewives are less likely to perform the above test due to their lower participation in the society and, as a result, their lack of awareness and financial dependence on their spouses [ 45 ]. Structural barriers such as low household incomes are an important determinant and make men unable to provide financial support to women.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some women in another Ethiopian study tended to give priority to diseases that present symptoms [ 51 ]. The studies conducted in high-income countries have also shown that feeling healthy is one of the barriers to participate in a CCS program [ 75 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though, WHO recommended screening of women aged 30-49years (24) and screening for cervical cancer between age 21 to 65years substantially reduces cervical cancer incidence (25), advanced stage of the disease (23), and mortality (22,23,25,26); still, there are different barriers that hinder the utilization of the screening services. Absence of linkage of diagnosis and treatment (6), traditional practices and beliefs (27,28), socioeconomic status (29)(30)(31), public awareness (31,32), fear of cancer and out-comes of screening (31)(32)(33), and health care access (30,31,33) are barriers of cervical cancer screening uptake mainly in LMICs. A few qualitative studies identi ed the lack of understanding of the bene ts of the screening as barriers to CC screening in LMICs (28,31).…”
Section: Introductionmentioning
confidence: 99%